FROM BARAKAH TO BUREAUCRACY: REFRAMING ORGANISATIONAL LEGITIMACY IN ISLAMIC EDUCATION THROUGH INSTITUTIONAL THEORY - Suheri Suheri (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The expansion of bureaucratic governance has repositioned accreditation, accountability, and regulatory compliance as dominant sources of organisational legitimacy in contemporary education. Institutional theory explains this development through regulative, normative, and cultural-cognitive pillars that shape organisational conformity. However, its adequacy in faith-based educational contexts remains insufficiently examined. This study critically reassesses institutional legitimacy theory through the case of Islamic education and proposes a conceptual extension. Employing a qualitative library-based design, the article systematically analyses foundational institutional theory alongside classical and contemporary scholarship on Islamic educational authority. The findings indicate that while bureaucratic rationality secures formal recognition, legitimacy in Islamic education is also grounded in perceived alignment with transcendent moral order, articulated through the concept of barakah. Reframed as spiritual capital, barakah functions as a source of communal trust and ethical credibility that operates beyond procedural compliance. The study advances a layered model of organisational legitimacy in which spiritual-moral legitimacy complements existing institutional pillars. By introducing vertical accountability to sacred values into institutional analysis, this article expands the theoretical scope of organisational legitimacy and contributes to broader debates on governance, rationalisation, and the persistence of religious authority within modern educational systems.